Audio in VR: Effects of a Soundscape and Movement-Triggered Step Sounds on Presence - Kern, Angelika C.; Ellermeier, Wolfgang (Frontiers in Robotics and AI, 2020)
For effective virtual realities, “presence,” the feeling of “being there” in a virtual environment (VR), is deemed an essential prerequisite. Several studies have assessed the effect of the (non-)availability of auditory stimulation on presence, but due to differences in study design (e.g. virtual realities used, types of sounds included, rendering technologies employed), generalizing the results and estimating the effect of the auditory component is difficult. In two experiments, the influence of an ambient nature soundscape and movement-triggered step sounds were investigated regarding their effects on presence. In each experiment, approximately forty participants walked on a treadmill, thereby strolling through a virtual park environment reproduced via a stereoscopic head-mounted display (HMD), while the acoustical environment was delivered via noise-cancelling headphones. In Experiment 1, conditions with the ambient soundscape and the step sounds either present or absent were combined in a 2x2 within-subjects design, supplemented with an additional ‘no-headphones’ control condition. For the synchronous playback of step sounds, the probability of a step being taken was estimated by an algorithm using the head-mounted display’s sensor data. The results of Experiment 1 show that questionnaire-based measures of presence and realism were influenced by the soundscape but not by the reproduction of steps, which might be confounded with the fact that the perceived synchronicity of the sensor-triggered step sounds was rated rather low. Therefore, in Experiment 2, the step-reproduction algorithm was improved and judged to be more synchronous by participants. Consequently, large and statistically significant effects of both kinds of audio manipulations on perceived presence and realism were observed, with the effect of the soundscape being larger than that of including footstep sounds, possibly due to the remaining imperfections in the reproduction of steps. Including an appropriate soundscape or self-triggered footsteps had differential effects on subscales of presence, in that both affected overall presence and realism, while involvement was improved and distraction reduced by the ambient soundscape only.